Thermal and viscous irreversibilities in the heat exchanger of individually finned heat pipes using freon R404A as the working fluid - Nogueira, Élcio (Mechanical Engineering Advances, 2023)
This work aims to apply a theoretical procedure to determine the performance of the heat exchanger of individually finned heat pipes used in an air conditioning system. The relevant physical quantities are defined and specified locally in the evaporator and condenser sections. The results obtained in the sections are associated with the theoretical determination of the global performance of the heat exchanger. Global theoretical results are compared with global experimental results. Thermal effectiveness, heat transfer rate, pressure drop, thermal and viscous irreversibilities, and thermodynamic Bejan number are determined at the evaporator, condenser, and heat exchanger. The relevant variables used to determine the results are the number of fins per heat pipe and rows of heat pipes. The theoretical-experimental comparison demonstrates that the localized model applied in the analysis is consistent and can be used as a design and comprehensive analysis tool for finessed heat exchangers. The performance of the heat exchanger demonstrated exceptionalness when comparing irreversibilities through the Bejan number, indicating a favorable cost-benefit ratio for the fins less than 30 and the number of heat pipes equal to 49. Bejan’s thermodynamic number, which uses results related to thermal and viscous irreversibilities, demonstrated that one should look for the relationship between thermal irreversibility versus total irreversibility and that fin numbers between 10 and 20 for heat pipes equal to 49 provide a better cost-benefit ratio. The absolute percentage errors obtained between theoretical and experimental values, for an experimental number of fins equal to 30, for the overall heat transfer rate and overall thermal effectiveness range from 2.0% to 42.1%.